PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS NUMERASI UNTUK SISWA SEKOLAH DASAR - Yunita Kristina; Yuyu Yuhana; Aan Subhan Pamungkas (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Advances in technology encourage teachers to become digital teachers who can innovate 21st-century learning. The development of instructional video media is a solution in creating active and popular learning today. Thinking critically, systematically, and logically in solving problems is part of numeracy, its simple ability to use mathematical sentences in everyday life. Therefore, the researcher developed an instructional video media through numeracy-based for grade III elementary school students at SDS Maria Mediatrik; the material for adding and decreasing fractions is the same. This study used the research and development (R&D) method with the ADDIE research model (analyzing, designing, developing, implementing, and evaluating). This study aimed to see the video development process, the feasibility of learning videos, students' responses to learning videos and provide provisions for understanding after using instructional videos. Numeracy-based. The validation of video learning media obtained 88.33% with the category "very feasibility" tested. Student responses get an average of 97.50% in the "very good" category. The understanding results show an average value of 81.25; thus, this study concluded that "the value exceeds the 75 criteria for the school's minimum completeness criteria (KKM)